TRAFFICKING IN THE PERSPECTIVE OF ISLAMIC LAW AND THE DRAFT CRIMINAL CODE - Azzah Hafizhah, Imam Kamaluddin (Ijtihad : Jurnal Hukum dan Ekonomi Islam, 2018)
Human trafficking is a crime that violates humanrights. Especially for women and children that is easy andprofitable to be exploited. In this modern era, it is stillcommon crime of human trafficking are where the actionis carried out in the form and a new mode increasinglymanipulated and structured. Indonesian government itselfparticipated in the eradication of this crime, which has beenregulated in article 297 of the Penal Code and updatedin the Draft Bill Draft Article 546 of the Criminal Code.This research aims to find out the crime of trafficking isin terms of Islamic law perspective and the perspective ofthe Penal Code Bill. Writing research use descriptive qual-itative type of method and a comparatif research-analysisthat makes comparisons the crime of trafficking issuesin the perspective of Islamic law and the draft CriminalCode. The results of this paper is the legal conformity ofthe crime of trafficking in the Draft Bill to the Islamic lawin the prosecution and combating such crime. In order tobecome a reference in law enforcement transnational crime,combating and stopping crime is not humane.